2012
DOI: 10.1097/brs.0b013e31824bac7a
|View full text |Cite
|
Sign up to set email alerts
|

Which Lenke 1A Curves Are at the Greatest Risk for Adding-On... and Why?

Abstract: Understanding the difference between Lenke 1A-L and 1A-R curve types may be helpful in preventing the adding-on phenomena postoperatively. To prevent adding-on in 1A-R curves, we recommend fusing distally to 1 level above the neutral vertebra or 1 to 2 levels above the stable vertebra. In 1A-L curves, adding-on may simply be a need to balance some lumbar curve progression in a young, skeletally immature patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 16 publications
3
79
1
Order By: Relevance
“…Skeletal immaturity and selection of LIV were found to be highly correlated with adding-on [4,22]. Distal adding-on has been found to be more common in Lenke 1A right curves subclassified by Miyanji et al [18,23]. To prevent adding-on in Lenke 1A right curves, Cho recommended selecting an LIV one level distal to NVs or one or two levels proximal to SV.…”
Section: Discussionmentioning
confidence: 93%
“…Skeletal immaturity and selection of LIV were found to be highly correlated with adding-on [4,22]. Distal adding-on has been found to be more common in Lenke 1A right curves subclassified by Miyanji et al [18,23]. To prevent adding-on in Lenke 1A right curves, Cho recommended selecting an LIV one level distal to NVs or one or two levels proximal to SV.…”
Section: Discussionmentioning
confidence: 93%
“…However, insufficient understanding of curve morphology and subsequent improper selection of fusion levels may result in suboptimal outcomes. Without adequate surgical planning and a thorough understanding of the complex three-dimensional characteristics of each patient's curve, complications such as ''adding-on'', decompensation, junctional kyphosis, or shoulder imbalance [1][2][3][4][5] can result. These complications can have a tremendous effect on the patient and can significantly increase healthcare costs and resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…While the authors have shown that fusion mass shift is one factor that influences postoperative adding on, they have not shown that minimizing fusion mass shift eliminates the problem. In fact, their own series still had a 21% incidence of adding-on, well within the incidence range (21% to 51%) they cite from other authors [1,7]. Clearly, other factors are at work.…”
Section: Where Do We Need To Go?mentioning
confidence: 61%